2004
DOI: 10.1159/000081983
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Regulation of Affect in Postpartum Depressed Mothers and Their Infants: An Overview

Abstract: Specific patterns of interaction emerging in the first months of life are related to processes regulating mutual affects in the mother-child dyad. Particularly important for the dyad are the matching and interactive repair processes. The interaction between postpartum depressed mothers and their children is characterized by a lack of responsiveness, by passivity or intrusiveness, withdrawal and avoidance, as well as a low level of positive expression of affect. Thus, an impaired capability to regulate the chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 178 publications
(111 citation statements)
references
References 104 publications
2
102
1
6
Order By: Relevance
“…Given the risk and demographic status of the sample and known associations between these and target parameters, a set of covariates was introduced to control for their effects [22,23,48,61]. Covariates included the categorical variables diagnosis of depression, infant gender and maternal education level, and the continuous variables age of infant, age of mother and number of children.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the risk and demographic status of the sample and known associations between these and target parameters, a set of covariates was introduced to control for their effects [22,23,48,61]. Covariates included the categorical variables diagnosis of depression, infant gender and maternal education level, and the continuous variables age of infant, age of mother and number of children.…”
Section: Methodsmentioning
confidence: 99%
“…Withdrawn and intrusive interaction styles often exhibited by depressed mothers were found to be associated with adverse infant outcomes, such as a generalized disengaged and passive affectivity and self-regulatory style as well as insecure attachment styles [19,20,21,22,23]. Mother-infant matching can be hampered by maternal depression [22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…There is an indication that maternal depression, particularly in the postpartum period, negatively affects the interaction quality between a mother and her infant [12,13] and, consequently, child development [14,15]. Easterbrooks et al [16] found a negative effect of maternal postpartum depression on two dimensions of EA, namely maternal sensitivity and structuring, when children were 7 years old, even when controlling for concurrent maternal depression.…”
Section: Introductionmentioning
confidence: 99%
“…Insgesamt betrachtet wird vielfach postuliert, dass die negativen Auswirkungen der mütterlichen Depression im Wesentlichen durch Störungen der Mutter-KindInteraktion vermittelt werden (Murray u. Cooper, 1997;Tronick u. Reck, 2009;Reck et al, 2004).…”
Section: Postpartale Depression Und Kindliche Entwicklungunclassified